(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
For the past two decades, The United Arab Emirates’ groundwater and soil have become at risk of contamination, over-extraction and over-irrigation. However, the declining water quality and modest irrigation practices in many areas pressured farmers to install packaged desalination equipment that caused significant increase in the salinity levels in the soil as well as in the surface levels, leading to contaminants percolation to the groundwater aquifers. This paper introduces ModeflowMap,an innovative GIS Solution developed for capturing groundwater parameters for thousands of wells and boreholes in Abu Dhabi and Dubai. This solution is designed as a primary effort to summarize the data relevant to the quantity, quality, chemical and biological properties, as well as the locationand type of groundwater resources. Such data helped track and analyse the status and uses of groundwater reserves. The findings assisted also in improving and promoting efficient use of water resources in both Emirates. Such comprehensive effort is necessary to fully understand the state of UAE’s groundwater and soil resources in order to support the development of effective policies and efficiently manage these resources. Among the key findings of this project is the strong link of differences in groundwater levels to areas of irrigation and agricultural activity. The analysis shows that areas with fast declining groundwater reserves coincide with the areas of highest groundwater abstraction for agricultural irrigation. In fact, the water level in groundwater monitoring wells has dropped by more than 20 meters in Remah, and by over 14 meters in the Liwa Crescent over the course of only 12 years.However, in some areas, this trend has reversed over the past few years – in Madinat Zayed for example, groundwater levels have risen since 2010 following a decline for many years, which can be mainly attributed to a reduction in agricultural activity.